Foreign Institutional Ownership and Dividend Policy - Muthoharoh, Luluk; Setianto, Rahmat Heru (Southeast Asian Business Review, 2023)
Increasing institutional investors in manufacturing companies encourage companies to be more wise in making financial decisions, including dividend policy. Dividend policy related to profits earned by the company will be distributed to shareholders in the form of dividends or saved as retained earnings for reinvestment purposes. This study aims to examine the effect of foreign institutional ownership on dividend policy. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2013-2017, with a total of 466 observations. The Generalized Method of Moment (GMM) logistic regression and dynamic panel data estimation model was used in this study, with the dependent variable being dividend policy and the independent variable being ownership of foreign institutions. The study shows that foreign institutional ownership has a positive effect on dividend policy.